Closed-form critical response of elastic-plastic shear building with viscous damper under pseudo-double impulse for simulating resonant response under near-fault fling-step motion - Akehashi, Hiroki; Takewaki, Izuru (Frontiers in Built Environment, 2022)
A set of approximate closed-form solutions of the maximum interstory drifts under the critical pseudo-double impulse (PDI) is derived for non-proportionally damped multi-story shear building models with bilinear hysteresis. The use of PDI and the closed-form solutions efficiently and accurately enable the capture of the critical responses of elastic-plastic multi-degree-of-freedom (MDOF) systems under the one-cycle sine wave, which substitutes for the main part of near-fault fling-step motions. The formulation of the closed-form maximum interstory drifts is based on the energy balance law. In the formulation, a quadratic function approximation of the damping force-interstory drift relation is introduced together with an updated mode-controlled energy-based approach (UMEA). While UMEA was proposed in the previous paper to derive the approximate maximum interstory drifts of undamped elastic-plastic MDOF systems under the critical PDI, it is extended so that it can be applied to non-proportionally damped MDOF systems. It is demonstrated that the proposed method can estimate the maximum interstory drifts of elastic-plastic non-proportionally damped MDOF systems under the critical PDI and the corresponding one-cycle sine wave with high accuracy. The estimation by the proposed method can be conducted much more efficiently and stably than the time-history response analysis (THRA). It is also shown that the hysteretic energy dissipation is not large enough to reduce the maximum interstory drifts. Finally, it is demonstrated that the proposed method can accurately estimate the maximum interstory drifts of elastic-plastic moment-resisting frames with viscous dampers under the resonant one-cycle sine wave.